Defending Deep Democracy: Three Elections- Three Surprises- Three Lessons - Hanappi, Hardy (Advances in Social Sciences Research Journal, 2025)
The goal of this paper is to use the experiences of three surprising election results in 1930, 1916 and 2024 to explain which lessons can be drawn for further development of humanity’s evolution. It turns out that deep changes in the organisation of self-governance will be needed to master the evolving crises of global capitalism, which during the last years has been morphing into authoritarian, global, absolute capitalism.